Investigation on gas hydrates formation and dissociation in multiphase gas dominant transmission pipelines - Sahith, S.J.K. (MDPI AG, 2020)
In this work, a gas hydrate formation and dissociation study was performed on two multiphase pipeline systems containing gasoline, CO2, water, and crude oil, CO2, water, in the pressure range of 2.5-3.5 MPa with fixed water cut as 15 using gas hydrate rocking cell equipment. The system has 10, 15 and 20 wt. concentrations of gasoline and crude oil, respectively. From the obtained hydrate-liquid-vapor-equilibrium (HLVE) data, the phase diagrams for the system are constructed and analyzed to represent the phase behavior in the multiphase pipelines. Similarly, induction time and rate of gas hydrate formation studies were performed for gasoline, CO2, and water, and crude oil, CO2, water system. From the evaluation of phase behavior based on the HLVE curve, the multiphase system with gasoline exhibits an inhibition in gas hydrates formation, as the HLVE curve shifts towards the lower temperature and higher-pressure region. The multiphase system containing the crude oil system shows a promotion of gas hydrates formation, as the HLVE curve shifted towards the higher temperature and lower pressure. Similarly, the kinetics of hydrate formation of gas hydrates in the gasoline system is slow. At the same time, crude oil has a rapid gas hydrate formation rate. Â© 2020 by the authors.